Feasibility Analysis And Scenario For Infrastructure Projects With Low Return on Investment In Indonesia - Reza Kazhimi; Eka Pria Anas (Syntax Literate, 2022)
As a developing country, Indonesia is currently rampant in implementing infrastructure development. However, there are infrastructure projects (especially toll road projects) that are included in the National Strategic Project (PSN) but have low financial feasibility. Despite this, they are economically and socially politically feasible, and require a particular strategy to ensure the project can still be implemented. The analysis will be conducted by conducting in-depth case studies on infrastructure projects with low investment feasibility in Indonesia. These case studies aim to obtain a clear picture of the problem and identify the best solution/strategy to improve the feasibility of the project, enabling its implementation. Additionally, the impact of implementing the best scenario on its financial feasibility will be determined. Based on the analysis results, shortening the toll road segment is the best scenario that offers the highest financial feasibility. The second alternative involves seeking construction support from the Government to complete the toll road from Besuki to Banyuwangi, which represents the final stretch of the toll road on Java Island. The provision of VGF (Viability Gap Funding) in the form of construction support aims to facilitate the connection of the Probolinggo-Banyuwangi toll road and ensure a profitable rate of return on investment for Toll Road Business Entities, who are the investors in this project.